Rehabilitation following cerebral anoxia: An assessment of 27 patients. (2nd January 2016) - Tazopoulou, Eva; Miljkovitch, Raphaële; Truelle, Jean-Luc; Schnitzler, Alexis; Onillon, Michel; Zucco, Thierry; Hawthorne, Graeme; Montreuil, Michèle
Abstract: Objectives : (1) To evaluate cognitive and emotional impairments, disability and quality-of-life for adults with cerebral anoxia institutionalized in residential care facilities. (2) To evaluate the efficacy of medication, psychotherapy, support group and therapeutic activities. Methods : Twenty-seven persons with cerebral anoxia were recruited, on average 8 years post-injury. Only 20 went through the whole study. Over three consecutive 2-month periods, they were assessed four times to evaluate: baseline observations (T1–T2), adjustment of their medication (T2–T3); and the effect of psychotherapy, support group and therapeutic activities such as physical and artistic or cultural activities usually proposed in the facilities involved (T3–T4). Examined variables at all time points were cognitive status, anxiety and depression, anosognosia, alexithymia, disability and quality-of-life. Results : All participants exhibited cognitive and emotional impairments comparable to those reported in the literature. Statistical analyses revealed good baseline stability of their condition and no significant effects of changes in medication (between T2 and T3). Conversely, following implementation of psychotherapy, support group and therapeutic activities (between T3 and T4), quality-of-life and social participation were significantly improved. Conclusion : Social participation and quality-of-life for persons instutionalized several years after cerebral anoxia were improved by psychotherapeutic and therapeutic activities.